P-094. Contribution to the study of lower lip carcinoma - Biazolla, E. R. [UNESP]; Furuse, C. F. [UNESP]; Pelissaro, G. S. [UNESP]; Collado, F. U. [UNESP]; Sandefeld, M. L.M.M. [UNESP] (My University, 2001)
Aim: Carcinoma of the lower lip may be diagnosed early, because it occupies an anatomical area that is easily accessible and visible. However, in literature there are still few articles about both epidemiological and clinical studies with regard to it. The aim of this work was to analyze variables that could influence the prognosis, incidence, complication arising from treatment and the interval of time between the appearance of the lesion and the diagnosis. Methods: An analysis was made of 31 cases treated at the Oral Cancer Center of the Paulista State University, Unesp, Aracatuba Campus, Brazil, during the period between January 1991 and July 1998. The following variables were observed: age, color, profession, sex, smoking, alcohol intake, time of lesion evolution, macroscopy, oral hygiene, clinical state, treatment therapy and complications. Results: Age varied between 27 and 79 years, all of the patients were white, 54.8% did not work under the sun, 93.5% were of the male, 61.2% smoked, 51.6% drank, 54.8% were diagnosed after 6 months of the lesion appearing, 74.2% were ulcers, 48.4% had very poor oral hygiene, 87.% were at stage I and II, all were submitted to surgery, 9.7% presented post operative complications, 77.4% were degree II. Conclusion: It was concluded that lip carcinoma has a good prognosis, profession did not influence its occurrence, smokers had greater possibility of postoperative complications and the diagnosis is made several months after the lesion has appeared.